PENGARUH PELATIHAN TERHADAP MOTIVASI KERJA DAN KINERJA KARYAWAN (PADA PT. PAL INDONESIA) - Aribowo, Handy; Givanni, Claudia Laurenza (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2023)
Indonesia is the largest archipelagic country in the world which has the potential to become the World Maritime Axis. One of the government's strategic steps is to give greater trust to the domestic defense industry to be able to make a major contribution to efforts to modernize the defense system. One of the government's supports is through State Capital Participation. In the last ten years, one of the State-Owned Enterprises for the defense industry in the maritime sector has received an injection of State Capital Participation funds by the government, namely PT. PAL Indonesia. In the realization of invests part of the State Capital Investment for the Training of Human Resources (HR). This study tested one independent variable, namely training and two dependent variables, namely work motivation and employee performance. This data collection method uses a questionnaire method to the employees of PT. PAL Indonesia as a respondent. The questionnaires distributed in this study were 95 questionnaires which were proven by the t test with the results showing that the significance level (α) was 0.001 indicating that the Training (X) which had been held by PT. PAL Indonesia is significant to Work Motivation (Y1). And the variable Training (X) has a significance level of 0.001 indicating Employee Performance (Y2). Keywords: Training, Work Motivation, Employee Performance, Human Resources